Green Capsicum annuum fruit extract for inhibition of mild steel corrosion in hydrochloric acid solution - Ji G.; Shukla S.K.; Dwivedi P.; Sundaram S.; Ebenso E.E.; Prakash R. (My University, 2025)
We are reporting green capsicum annuum fruit extract as inhibitor for mild steel corrosion in acid solution. Inhibition potential of this aqueous fruit extract has been determined with the help of weight loss method and electrochemicaltechniques. Results obtained by various techniques are close to each other and maximum efficiency of 85 % is acknowledged at the inhibitor concentration of 1400 mgl-1. Langmuir isotherm model is found most suitable to explain adsorption behavior of inhibitor for mild steel surface. Molecular adsorption of inhibitor over mild steel surface is found responsible for corrosion inhibition of mild steel in acid which is also supported by OEM studies. © 2012 by ESG.